Biochemical Functions of Glutathione S-Transferase Family of Salix babylonica - Zhuge, Xiang-Lin; Xu, Hui; Xiu, Zhi-Jing; Yang, Hai-Ling (Frontiers in Plant Science, 2020)
Glutathione S-transferases (GSTs) are ubiquitous enzymes that are encoded by a large gene family, and they contribute to the detoxification of endogenous or xenobiotic compounds and oxidative stress metabolism in plants. Although the GSTs gene family has been reported in many land plants, our knowledge of the evolution and function of the willow GSTs is still limited. In this study, 22 full-length GST genes were cloned from Salix babylonica and divided into three classes based on the conserved domain analysis, phylogenetic tree and gene structure: tau, phi and DHAR. The tissue-specific expression patterns were substantially different among the tau and phi GSTs. The Salix GST proteins showed functional divergences in the substrate specificities, substrate activities and kinetic characteristics. The site-directed mutagenesis studies revealed that a single amino acid mutation (Ile/Val53→Thr53) resulted in the lowest activity of SbGSTU7 among the Salix GSTs. These results suggest that non-synonymous substitution of an amino acid at the putative glutathione-binding site may play an important role in the divergence of enzymatic functions of Salix GST family.